Phagocytosis - Swanson, Joel (Henry Stewart Talks, 2009)
Phagocytic cells, The movements of Fc receptor-mediated phagocytosis, Complement receptors, Receptors associated with phagocytosis, Movements of the actin cytoskeleton, Many routes of entry into cells, Coordination of signaling for phagocytosis, How phagocytosis relates to immunity